Análisis sistemático sobre estrés laboral en Colombia (2021)
The purpose of this research was to prepare a documentary review in an exhaustive way on the different articles found in psychological journals and repositories at national level on occupational stress in Colombia (2013-2018). It analyzed and highlighted from a psychosocial approach the concept of occupational stress, the main models that try to explain this phenomenon, the causes and harmful consequences that originate in the individual and in the organization. A great number of articles on the subject were found in repositories, since in total there were 29 out of 55 data. Based on the results, it could be observed that 2014 and 2017 were the two years where more journals on occupational stress were obtained and the cities where most of the journals found that referred to the investigated topic were Medellin and Bogota, equivalent to 69.09 % of the total data.